PENGEMBANGAN MODEL PEMBELAJARAN PERMAINAN SEPAK BOLA GAWANG SIMPAI MELALUI PENDEKATAN PERKEBUNAN PADA SISWA KELAS V SD NEGERI 01 GADU KECAMATAN GUNUNGWUNGKAL KABUPATEN PATI (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study is to determine the game of football modified form corresponding to fifth gradestudents Elementary School 01 Gadu Gunungwungkal District regency Pati.The method of research is the development of a model refers to the development of Borg & Gall has beenmodified. Data collection was done using expert evaluation sheet (one expert and one expert penjas learning),testing a small group (10 students), and large-scale test (20 students). The data analysis technique used isdescriptive percentage to reveal aspects of psychomotor, cognitive, and affective student after using the product.From the test results obtained by the expert evaluation data, expert penjas 82% (good), a Learning 93% (verygood), a small test group 88% (good), and a large group trial 93% (very good). From the available data it canbe concluded that the development of learning through play football goal hoops can be used in the learningprocess of students penjasorkes Elementary School 01 Gadu.Based on the results of research and discussion, it can be concluded that the game of football goal hoopseffective, so it can be applied as a model of learning in the learning penjasorkes.